Non-invasive Mapping of Face Processing by Navigated Transcranial Magnetic Stimulation - Maurer, Stefanie; Giglhuber, Katrin; Sollmann, Nico; Kelm, Anna; Ille, Sebastian; Hauck, Theresa; Tanigawa, Noriko; Ringel, Florian; Boeckh-Behrens, Tobias; Meyer, Bernhard; Krieg, Sandro M. (Frontiers in Human Neuroscience, 2017)
Background: Besides motor and language function, tumor resections within the frontal and parietal lobe have also been reported to cause neuropsychological impairment, like prosopagnosia. Objective: Since non-navigated transcranial magnetic stimulation (TMS) has previously been used to map neuropsychological cortical function, this study aims to evaluate the feasibility and spatial discrimination of repetitive navigated TMS (rTMS) mapping for detection of face processing impairment in healthy volunteers. The study was also designed to establish this examination for preoperative mapping in brain tumor patients. Methods: Twenty healthy and purely right-handed volunteers (11 female, 9 male) underwent rTMS mapping for cortical face processing function using 5 Hz/10 pulses. Both hemispheres were investigated randomly with 2 weeks delay. Fifty-two predetermined cortical spots of the whole hemispheres were mapped after baseline measurement. The task consisted of 80 portraits of popular persons, which had to be named while rTMS was applied. Results: In 80% of all subjects rTMS elicited naming errors in the right middle middle frontal gyrus (mMFG). Concerning anomia errors, the highest error rate (35%) was achieved in the bilateral triangular inferior frontal gyrus (trIFG). With regard to similar or wrongly named persons, we observed 10% error rates mainly in the bilateral frontal lobes. Conclusion: It seems feasible to map the cortical facial processing function and to generate face processing impairment via rTMS. The observed localizations are well in accordance with the contemporary literature, and the mapping did not interfere with rTMS-induced language impairment. The clinical usefulness of preoperative mapping has to be evaluated subsequently.